Coil-assisted ethanol embolization of traumatic arteriovenous fistulas: a 10-year retrospective study - Shen, Yuchen; Han, Qianyun; Wang, Deming; Su, Lixin; Wen, Mingzhe; Fan, Xindong; Yang, Xitao (Frontiers in Cardiovascular Medicine, 2024)
This study aimed to evaluate the efficacy and safety of ethanol embolization in treating traumatic arteriovenous fistulas (TAVFs).From March 2012 to April 2020, 42 consecutive patients (29.9±15.1 years, range: 3-68 years) with peripheral TAVFs underwent ethanol embolization. All patients underwent clinical and imaging follow-up (40.0±25.9 months, 3-90 months). The mean time to onset of symptoms after trauma was 5.4±5.9 months (range: 0.5-30 months). In total, 27 (64.3%) reported that the TAVFs were presented after blunt trauma, 10 (23.8%) were shown after penetrating trauma (4 patients were penetrated with infusion indwelling needles), and 3 (7.1%) had surgery history. Treatment effects, devascularization rate, and complications were evaluated at follow-ups at 1-3 months intervals.Results: Seventy-one embolization procedures were conducted, with a mean of 1.6±0.7 procedures per patient. Thirty-four patients received coil-assisted ethanol embolization;Absolute ethanol was administered in all procedures, with an average volume of 7.1±4.2mL per procedure (range: 1-18 mL); 28 patients (28/42, 66.7%) received coil embolization in 36 procedures (36/71, 50.7%). In reexamination, 39 patients (92.9%) achieved 100% devascularization; 29 out of 39 patients (74.4%) with Schobinger Stage II TAVFs had improved to Stage I or asymptomatic. Finally, 30 cases (66.7%) achieved complete response, and the other 12 (33.3%) showed partial response. Besides, apart from minor complications, no major complications were observed postoperatively.Coil-assisted ethanol embolization can effectively manage TAVFs with 4 an acceptable risk of mild complications.